The Branch-and-bound Method, Genetic Algorithm, and Dynamic Programming to Determine a Safe Ship Trajectory in Fuzzy Environment - Mostefa, Mohamed-Seghir (Procedia computer science, 2014)
The paper describes methods based on the branch-and-bound method, dynamic programming and genetic algorithm to determine a safe ship trajectories in the collision situation in fuzzy environment. Optimal safe ship trajectory in collision situation is presented as multistage decision-making in a fuzzy environment. The maneuverability parameters of the ship and the navigator's subjective assessment in making a decision are taken under consideration in the process model.